Age validation of canary rockfish (Sebastes pinniger) from off the Oregon coast (USA) using the bomb radiocarbon method - Piner, K. R.; Hamel, O. S.; Menkel, J. L.; Wallace, J. R.; Hutchinson, C. E. (Canadian Journal of Fisheries and Aquatic Sciences, 2005)
The alternating translucent and opaque banding pattern in canary rockfish (Sebastes pinniger) otoliths, aged using a break-and-burn methodology, are annual markings. To validate age assignment, we compared measured radiocarbon levels in canary rockfish otolith cores with a reference chronology developed from known age Pacific halibut (Hippoglossus stenolepis). An average 2- to 3-year phase shift was detected between the canary rockfish and a Pacific halibut reference chronology that was likely the result of differences in the regional oceanography or underageing bias. The assumption of ageing bias consistency was tested with two sampling designs. The first design controled for age-related ageing error, and the second design related birth year to estimated age. No change in the magnitude of ageing bias as a function of age was detected.
932zxTimes Cited:27Cited References Count:27